Health information management practices in informal caregiving: An artifacts analysis and implications for IT design. (December 2018) - Holden, Richard J.; Karanam, Yamini L.P.; Cavalcanti, Luiz Henrique; Parmar, Takshak; Kodthala, Prasanthi; Fowler, Nicole R.; Bateman, Daniel R.
Highlights: Informal caregivers perform personal health information management (PHIM). Caregivers' PHIM practices support daily care management and decision-making. Caregivers acquire, integrate, maintain, update, use, and communicate information. PHIM challenges include information workload and integrating PHIM into daily life. Tools such as CARE Kit assisted informal caregivers in managing health information. Abstract: Introduction: Unpaid informal caregivers of adult care recipients, including persons with dementia, experience multiple unmet information needs and information management challenges. Objectives: To understand the current personal health information management (PHIM) practices in informal caregiving for adults with and without dementia. Methods: Semi-structured interviews were performed with ten informal caregivers—half of whom were caring for persons with dementia—and four formal caregivers at an adult day service. Interviews centered on a paper-based tool distributed by the day service, the CARE Kit, permitting an artifacts analysis of the tools used by participants for PHIM. Qualitative thematic analysis was applied to interview data. Results: Caregivers' PHIM practices aimed to support daily care management and decision-making on behalf of care recipients, through: 1) information acquisition and integration across multiple sources and records; 2) information maintenance, updating, and use over time; and 3) information sharing and communication with healthcare professionals and other family caregivers. Participants reported advantages and challenges of their PHIM practices and tools, including fitting PHIM into their daily lives, managing PHIM-related cognitive workload, the functionality of PHIM tools, and the dynamic, longitudinal nature of PHIM. Conclusion: The study produced a number of implications for caregiver health information management information technology (CHIM IT), based on findings about the nature of caregivers' practices for managing information for adult care recipients. We present CHIM IT requirements related to privacy and security, customization and flexibility, ease of use, credibility and sensitivity, situation awareness, information integration, delegation and shared use, updating and maintenance, archiving and versioning, communication, agency and information access, and validation.